Intramedullary Fixation Does Not Cause a Large Amount of Hidden Blood Loss in Elderly Patients with Intertrochanteric Fractures - Guo J; Zhang Y; Hou Z (Clinical Interventions in Aging, 2021)
Junfei Guo,1,2 Yingze Zhang,1– 3 Zhiyong Hou1,2 1Department of Orthopedic Surgery, Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People’s Republic of China; 2NHC Key Laboratory of Intelligent Orthopaedic Equipment (The Third Hospital of Hebei Medical University), Shijiazhuang, People’s Republic of China; 3Chinese Academy of Engineering, Beijing, 100088, People’s Republic of ChinaCorrespondence: Zhiyong HouThird Hospital of Hebei Medical University, Department of Orthopaedic Surgery, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaTel +86-18533112800Fax +86-0311-8702362Email drzyhou@gmail.comPurpose: Controversy remains around intramedullary fixation of intertrochanteric fractures in elderly patients when considering hidden blood loss (HBL). However, whether treating the fractures with intramedullary fixation causes a large amount of HBL is not known.Patients and Methods: In this retrospective cohort study, 1,017 consecutive patients aged ≥ 65 years with acute intertrochanteric fractures were included and assigned to three groups (non-operative group, delayed surgery group, and acute surgery group) between July 2013 and January 2018. The data of patients’ demographics, injury-related data, operation-related data, comorbidities, perioperative hemoglobin values, transfusion data and serial of HBL calculated during hospitalization were collected and compared among three groups. All independent variables were further analyzed by multiple linear regression to evaluate the influential factors of HBL. A long-term follow-up was conducted and survival analysis was performed for all individuals.Results: Our results showed that fixation by proximal femoral nail anti-rotation for intertrochanteric fracture has been estimated to contribute 11– 34% of the increase of HBL during hospitalization and it does not increase the allogeneic transfusion rate. For HBL, male patients, unstable fracture, and blood transfusion may have strong influences. Surgical delay was associated with longer time from injury to hospital admission, higher ASA-grade, and comorbidities such as diabetes and coronary heart disease. Survival analysis revealed that mortality increased in patients with conservative treatment, where a rapid decline was found in the first year, especially in the 90 days after injury. A higher mortality rate was also obtained in patients with surgery delay than acute surgery patients.Conclusion: In conclusion, HBL is the main component of total blood loss and it is more likely to result from the initial trauma rather than the surgery. Intertrochanteric fracture treated by intramedullary fixation does not cause a large amount of HBL.Keywords: hidden blood loss, intertrochanteric fracture, elderly, multiple linear regression, survival analysis